Kajian Pedagogik dalam Implementasi STEAM pada Pembelajaran Jarak Jauh di Era Pandemi - Bella Iaskyana; Cepi Triatna; Nurdin Nurdin (SAP (Susunan Artikel Pendidikan), 2022)
The outbreak of the pandemic COVID-19 requires Indonesia to make a new policy related to Distance Learning, in which students and teachers are able to interact over the internet without having to come to school. In this condition, teachers as an educator are required to be able to plan and manage the online classes in creative and innovative ways. It's important for educators to decide on a suitable model or media to build students' interest. The STEAM approach is used to facilitate online learning by leveraging the fields of science, technology, engineering, arts, and mathematics and fostering 21stcentury skills. This study analyzes pedagogical studies including models, media, and technology used in online learning. The methodology used was a literature study review with content analysis on the implementation of the STEAM approach from 2020 to 2022. The results of the analysis were interpreted using percentages and descriptive analysis to obtain conclusions. This study found that the learning model commonly used in the STEAM approach was Project-Based Learning with the expectation of improving students' thinking skills. The media and technology commonly used in online learning are Google Classroom and video conferencing such as Google Meetings or Zoom Meetings. The implementation of the STEAM approach shows a positive impact on increasing students' potential, such as improving learning outcomes and improving 21st-century skills.